Analisis Proses Penyusunan Program Kerja Pengawasan Tahunan (PKPT) Berbasis Risiko di Inspektorat Daerah Kabupaten Bandung - Putra Rizki Octaviano; Hn Hartikayanti (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the process of preparing a Risk-Based Annual Supervision Work Program (Program Kerja Pengawasan Tahunan/PKPT) at the Regional Inspectorate of Bandung Regency. Risk-based supervision is considered essential to improve the effectiveness and efficiency of internal control, particularly in response to limited resources of Government Internal Supervisory Apparatus (APIP) and the increasing complexity of risks in regional financial management. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews with the PKPT drafting team, observation, and documentation review of supervision planning documents and relevant regulations. The results indicate that the preparation of the risk-based PKPT has been conducted in accordance with the Risk-Based Supervision Planning Guidelines (PPBR) issued by BPKP, starting from the development of the audit universe, risk assessment, to the determination of supervision priorities. However, several challenges remain, including suboptimal risk identification and mapping across all regional work units, limited support from information systems or applications, and delays in central government supervision policies that affect the finalization of the PKPT document. This study concludes that although the risk-based PKPT preparation at the Regional Inspectorate of Bandung Regency has been implemented in line with the regulatory framework, improvements are still needed in risk management practices, inter-agency coordination, and the utilization of information technology to enhance the effectiveness and focus of internal supervision.